62 Which Indices Demonstrate Changes in Diastolic Function During Sub-Maximal Exercise Testing?. (31st May 2014) - Erdei, Tamas; Edwards, Julie; Braim, Delyth; Yousef, Zaheer; Fraser, Alan
Abstract : Patients with heart failure with preserved ejection fraction (HFPEF) often have symptoms only during exercise, which are assumed to be caused by impaired functional reserve. Diastolic stress testing is now recommended, but it is uncertain which indices can identify abnormal responses. Methods: 29 subjects (>60 yrs) underwent diastolic stress testing, including 10 patients with HFPEF (4 males) and 8 age-matched healthy controls (4 males). HFPEF was diagnosed in accordance with the consensus statement of the ESC (signs or symptoms of heart failure and EF >50% and evidence of diastolic dysfunction). A ramped exercise protocol on a semi-supine bicycle, starting at 15 W with 5 W increments every minute, was paused at constant submaximal workload when the patient developed symptoms or while heart rate was 100–110/min (whichever was earlier). Diastolic filling was assessed by measuring early diastolic velocities using pulsed-wave and colour myocardial velocity imaging (MVI), and flow propagation velocity (Vp). Changes in mean filling pressure were estimated by E/e'. Longitudinal systolic function was measured by pulsed and colour MVI. Results: At rest, long-axis early diastolic velocities were similar in HFPEF patients to controls (pulsed MVI: e'lat:6.7 ± 1.8 vs 8.2 ± 2.7 cm/s; e'sept: 5.3 ± 1.4 vs 6 ± 0.9 cm/s; colour MVI: Ve-bp:3.9 ± 1.6 vs 4.9 ± 2.5 cm/s; Ve-bas: 3.4 ± 0.9 vs 3.7 ± 0.64 cm/s; all NS) but during sub-maximal exercise they were lower (e'lat:10.3 ± 2.1 vs 13.8 ± 4.3 cm/s, p < 0.05; e'sept: 7.4 ± 1.4 vs 11 ± 2.6 cm/s, p < 0.05; Ve-bp: 5.4 ± 2.1 vs 8.1 ± 2.6 cm/s, p < 0.05; Ve-bas: 4.3 ± 1.7 vs 6.4 ± 1.3 cm/s, p < 0.05). Mean Vp did not change significantly from rest to exercise in HFPEF patients (+35% from 59 ± 20 to 80 ± 37 cm/s, NS) whereas it increased by 56% in controls (67 ± 39 vs 103 ± 50 cm/s; p < 0.05). E/e' (average of medial and lateral sites) did not change at submaximal exercise in HFPEF (11.2 ± 4.2 vs 10.1 ± 2.8, NS) while it increased in controls (7.9 ± 2.8 vs 9.1 ± 3.4, p < 0.05); the increments of E/e' were -1.0 ±. 6 in HFPEF compared with +1.2 ± 0.4 in controls (p < 0.05). Long-axis systolic velocities at rest were similar in HFPEF and controls (s'lat: 7.8 ± 1 vs 7.6 ± 1.3 cm/s; s'sept: 7.1 ± 1.4 vs 7.1 ± 1.1 cm/s, all NS) but systolic velocities on exercise were lower in HFPEF (8.9 ± 1.7 vs 10.8 ± 1.7 cm/s; p < 0.05). Conclusions: This study suggests that e' and Vp demonstrate impaired diastolic functional reserve in HFPEF, possibly related to delayed untwisting and reduced suction. Although E/e' is a criterion that is recommended for diagnosing HFPEF, in these subjects it demonstrated changes during submaximal exercise that were opposite to those expected, raising doubts about its utility for discriminating patients with HFPEF from age-matched controls.